Key Generation Techniques to Ensure User Data Integrity in Cloud Environments - Su Jeong, Yoon; Ho Lee, Sang (International Journal of Engineering and Technology, 2018)
Background/Objectives: Cloud services are becoming popular with many users as they provide services based on the Internet. Users who use cloud services can integrate computing resources such as hardware and software, which exist in intangible form, through virtualization technology, and there is a great demand for security technologies related to security problems.Methods/Statistical analysis: As a result of the evaluation, the proposed method in the security evaluation and the performance evaluation resulted in better data integrity and security than the existing method. In addition, we checked the integrity of different cloud data and obtained the efficiency improved by O (logn) than the existing method.Findings: In this paper, we propose a robust data integrity protection scheme for various security attacks in the cloud environment. The proposed method effectively guarantees the integrity of the data used by the user through the generation and processing of low-load keys between the TPA, the user and the KGC. To protect the integrity of the data transmitted and received in the cloud environment, the proposed method generates the key through three processes (data generation process, encryption key generation process, and metadata attribute key pair generation process).Improvements/Applications: The key generated in this process is used by the anonymous key so that sensitive information of the cloud user is not exposed to a third party so that the important information of the user is not remembered. In addition, the proposed scheme keeps synchronization between the TPA and the user at a predetermined time interval so that the important information of the user is not illegally exploited from the third party.Â Â